Akademickie Związki Sportowe jako droga do rozwoju aktywności sportowej wśród studentów śląskich uczelni = University Sports Association as the way to sport activity development among Silesian students - Mędrak, Anna; Rżany, Michał; Otremba, Barbara; Brodowska, Elwira; Szynal, Magdalena; Alcer, Magdalena; Górecka, Anna; Stefaniak, Tomasz; Suszyński, Krzysztof; Górka, Dariusz (Journal of Education, Health and Sport, 2015)
Mędrak Anna, Rżany Michał, Otremba Barbara, Brodowska Elwira, Szynal Magdalena, Alcer Magdalena, Górecka Anna, Stefaniak Tomasz, Suszyński Krzysztof, Górka Dariusz. Akademickie Związki Sportowe jako droga do rozwoju aktywności sportowej wśród studentów śląskich uczelni = University Sports Association as the way to sport activity development among Silesian students. Journal of Education, Health and Sport. 2015;5(11):616-628. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35711 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A616-628 http://pbn.nauka.gov.pl/works/684931 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Mędrak Anna, Rżany Michał, Otremba Barbara, Brodowska Elwira, Szynal Magdalena, Alcer Magdalena, Górecka Anna, Stefaniak Tomasz, Suszyński Krzysztof, Górka Dariusz. Akademickie Związki Sportowe jako droga do rozwoju aktywności sportowej wśród studentów śląskich uczelni. Quality in Sport. 2015;1(3):38-49. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Anna Mędrak, Michał Rżany, Barbara Otremba, Elwira Brodowska, Magdalena Szynal, Magdalena Alcer, Anna Górecka, Tomasz Stefaniak, Krzysztof Suszyński, Dariusz Górka Zakład Medycyny Sportowej i Fizjologii Wysiłku Fizycznego, Katedra Fizjoterapii, Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach Akademickie Związki Sportowe jako droga do rozwoju aktywności sportowej wśród studentów śląskich uczelni University Sports Association as the way to sport activity development among Silesian students Streszczenie Wstęp. Regularna aktywność fizyczna i prawidłowe odżywianie to dwa fundamentalne filary filozofii zdrowego stylu życia. Rozwój aktywności fizycznej wśród studentów uwarunkowany jest wieloma złożonymi czynnikami, wśród których wyróżniamy: profil studiów, dostęp do infrastruktury sportowej oraz możliwość brania udziału w zajęciach sportowych organizowanych przez kluby czy Akademickie Związki Sportowe. Cel pracy. Celem pracy była analiza czynników mających wpływ na samoocenę aktywności fizycznej studentów. Postawiono następujące pytania badawcze: Czy wybór uczelni ma związek z dostępem do zajęć organizowanych przez Akademickie Związki Sportowe? Czy branie udziału w zajęciach organizowanych przez AZS ułatwia rozwój sportowy? Czy istnieje zależność pomiędzy lokalizacją miejsc, w których organizowane są zajęcia sportowe, godzinami odbywania się zajęć sportowych, rodzajem i formą zajęć sportowych a korzystaniem z oferty AZS? Materiały i metody. W badaniach wzięło udział 395 studentów, w tym 257 kobiet w wieku od 18 do 27 lat (x=20,7; SD=1,4) i 108 mężczyzn w wieku od 18 do 26 lat (x=21; SD=1,45). Wśród badanych znaleźli się studenci z pięciu śląskich uczelni wyższych. Metodą zastosowaną w trakcie badania była anonimowa ankieta składająca się z 37 zamkniętych pytań, które dotyczyły następujących kwestii: formy podejmowanej aktywności fizycznej, Akademickich Związków Sportowych oraz wpływu obranego kierunku studiów na rozwój aktywności fizycznej. W 21 pytaniach w ankiecie posłużono się skalą Likerta. Opracowanie statystyczne obejmowało wykonanie statystyk opisowych, natomiast poziom różnic określono za pomocą analizy wariancji ANOVA. Wyniki. Analiza statystyczna wykazała istotną zależność pomiędzy rodzajem uczelni a lokalizacją miejsc w których odbywają się zajęcia organizowane przez AZS (p=0,04). Rodzaj uczelni natomiast nie wpływa na czynniki takie jak: godziny w których odbywają się zajęcia sportowe (p=0,07) oraz rodzaj zajęć sportowych znajdujących się w ofercie (p=0,39). Istnieje istotna zależność miedzy rodzajem uczelni a rezygnacją z uprawiania sportu (p=0,0002). Najczęściej muszą z niego rezygnować studenci Śląskiego Uniwersytetu Medycznego, a najrzadziej Uniwersytetu Śląskiego. Istnieje również zależność między podejściem do uprawiania sportu a rodzajem uczelni (p=0,01). Najbardziej ułatwia karierę sportową Uniwersytet Ekonomiczny w Katowicach. Wnioski: Podejmowanie aktywności fizycznej przez studentów jest zależne od lokalizacji uczelni oraz miejsc, w których odbywają się zajęcia. Czynniki takie jak godziny odbywania się zajęć, oraz rodzaj zajęć nie są zależne od rodzaju uczelni. Rodzaj uczelni ma wpływ na rezygnację z uprawnia sportu. Słowa kluczowe: aktywność fizyczna, Akademickie Związki Sportowe. Abstract Introduction. There are two fundaments of healthy lifestyle philosophy: regular physical activity and proper diet. The development of physical activity among students is determined by many complex factors. We can distinguish certain aspects such as university profile, access to the sport facilities and the opportunity to participate in sport activities which are organized by sport clubs or University Sports Association. The aim of the study. The aim of the study was to analyze the factors that affect self-assessment of students physical activity. The following questions have been asked: 1.Is the choice of the university related to the access to sport activities which are organized by University Sport Association? 2.Does the participating in activities, which are organized by University Sport Association, help in physical development? 3.Is there any relation between the location, time, type, the way of sport activities which are offered by University Sport Association and participating in them? Material and methods. 395 students took part in research: 257 women (18-27 years old) (x=20,7 ; SD=1,4) and 108 men (18-26 years old) (x=21; SD=1,45). All the students are from five Silesian universities. Method used for the research was the anonymous questionnaire consisting of 37 questions which concerned: the way of the physical activity taken by students, the issue of University Sport Association and the influence of the university profile on physical activity development. The Likert scale was used in 21 questions. Statistical description included descriptive statistics. Degree of difference was defined by ANOVA analysis. Results. Descriptive analysis showed significant dependence between the type of the university and the location of sport facilities (p=0,04). The type of the university has no influence on the factors like: time (p=0,07) and type of sport activities offered by University Sport Association (p=0,39). There is also an important connection between the type of the university and resignation from doing sport (p=0,0002). Mostly – Medical University of Silesia students, least frequently – University of Silesia students. There is dependence between approach to doing sport among students and the type of university (p=0,01). The university which helps the most in sport career is University of Economics in Katowice. Conclusions: 1.Taking the physical activity by student depends on location of the university and sport facilities. 2.The factors such as time and type of sport activities are not related to the type of the university. 3.The type of the university influence the resignation from doing sport by students. Key words: physical activity, University Sports Association.